2023
DOI: 10.1134/s1064229323600847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Addition on Rhizosphere Soil Microbial Community and Yield of Wheat in Loess Plateau

Y. Q. Fan,
Q. Liu,
R. X. Huo
et al.

Abstract: The soil microbial community diversity of wheat rhizosphere was affected by the amount of nitrogen fertilizer. In addition to bacterial community, ammonia-oxidizing archaea, nitrogen-fixing bacteria and denitrifying bacteria also play important roles in nitrogen cycle. At present, the microecological mechanism of its response to nitrogen application is still unclear. In this study, the rhizosphere soil microorganisms of winter wheat were used as the research object.The changes of soil bacteria, ammonia-oxidizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Contrary to these findings, this study observed a decrease in MBC and MBN with N addition in all cases, except for B. napus when used as a single cover crop. This decline is primarily attributed to the accumulation of soil N induced by N addition, resulting in an imbalanced C:N:P ratio [42,43], leading to a reduction in soil microbial community diversity, particularly affecting functional microbial communities related to the N cycle. Single cover cropping the cruciferous crop B. napus with N addition increased both aboveground biomass and soil MBN by meeting its high N demands.…”
Section: N Addition Inhibited Microbial Carbon Biomass In the Rfc Systemmentioning
confidence: 99%
“…Contrary to these findings, this study observed a decrease in MBC and MBN with N addition in all cases, except for B. napus when used as a single cover crop. This decline is primarily attributed to the accumulation of soil N induced by N addition, resulting in an imbalanced C:N:P ratio [42,43], leading to a reduction in soil microbial community diversity, particularly affecting functional microbial communities related to the N cycle. Single cover cropping the cruciferous crop B. napus with N addition increased both aboveground biomass and soil MBN by meeting its high N demands.…”
Section: N Addition Inhibited Microbial Carbon Biomass In the Rfc Systemmentioning
confidence: 99%